Sensors for fire gas detectors - Kozubovsky, V.R.; Kormosh, V.V.; Alyakshev, I.P.; Lishchenko, N.H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Considered in this paper are the possibilities to reduce energy consumption in
semiconductor gas sensors with the purpose of their application in multichannel fire gas
detectors and gas alarms with an independent power supply.